Ten years later: A comparative perspective on HRM issues in foreign-affiliated firms in CEE (case of Slovakia) - Soňa Ferenčíková (Journal for East European Management Studies, 2000)
This paper is based on a 1999 survey of the largest foreign investors in the Slovak Republic. The main objective of the study is to measure the impact of foreign investors' human resource management practices on local companies and their environment in a more detailed way, to identify key problems in the human resource function in FDI-invested companies in Slovakia, and to describe the strategies that companies use to handle these problems. – – Die Grundlage für diesen Artikel bildet eine Übersicht über die größten Auslandsinvestoren in der Slowakischen Republik. Der Hauptgegenstand der Studie besteht in einer Messung des Einflusses, den die verschiedenen Formen des Humankapitalmanagement der Auslandsinvestoren auf lokale Unternehmen und deren Umfeld ausübt. Es geht um eine Identifizierung der Schlüsselprobleme des Humankapitalmanagement in Unternehmen mit direkter ausländischer Beteiligung in der Slowakei und um eine Beschreibung der Strategien, die Unternehmen anwenden um diese Probleme zu lösen.
Keywords: 650